Violence in the Model City : the Cavanagh administration, race relations, and the Detroit Riot of 1967 - Fine, Sidney, 1920-2009 (Michigan State University Press, 2007)
On July 23, 1967, the Detroit police raided a blind pig (after-hours drinking establishment), touching off the most destructive urban riot of the 1960s. It took the U.S. Army, the Michigan National Guard, the Michigan State Police, and the Detroit police department - 17,000 men - more than a week to restore order. When all was done, the riot had claimed 43 lives (mostly Black) and resulted in nearly 700 injuries. Over 7,000 individuals were arrested, with property damage estimates over 75 million. Yet, Detroit had been lauded nationally as a "model city" in the governance of a large industrial metropolis. The author presents a detailed study of what happened in Detroit, why, and with what consequences